A matematikai szorongás személyen belüli tényezőinek vizsgálata középiskolás tanulóknál - Nótin, Ágnes; Páskuné Kiss, Judit; Kurucz, Győző (Magyar Pedagógia, 2012)
Mathematics knowledge has a great influence on the effective functioning of social and economic systems today (Ashcraft and Krause, 2007). Mathematics education plays a very important role although children tend to dislike maths during their school years (Dienes, 1973) and often avoid maths-related careers (Wigfield and Meece, 1988). Maths anxiety lies at the heart of the problem, according to researchers (Richardson and Suinn, 1972; Ashcraft, 2002; Zakaria and MohdNordin, 2008; Karimi and Venkatesan, 2009). Maths anxiety is an acquired emotional response in everyday situations and in school when a person faces a mathematical problem. It has a negative influence on learning and performance and may be accompanied by emotional, physiological, cognitive, and behavioural symptoms as well. The problem is based on the following factors: situational factors (e.g. classroom activity, test, exam, everyday situations), social/environmental factors (e.g. school environment, teaching methods, the personality of the teacher), and personal factors (e.g. self-efficacy, self-concept, skills, early experiences) (Baloglu and Kocak, 2006). In our research, we focused on the personal factors that lie behind maths anxiety. The variables were maths anxiety, maths grades, attitude towards maths, trait anxiety, self-concept, and self-efficacy. In the first study, we used our own math anxiety questionnaire, the Maths Anxiety Assessment Test (MSzMT), to test secondary school pupils (N=89). The second study investigated the dynamic of maths anxiety and connections between personal factors. We assessed maths anxiety and the other personal factors in Year 9 schoolchildren (N=174) in three secondary schools. The data analyses confirmed our hypothesis because we found a positive correlation between maths anxiety and trait anxiety (.26) as well as between self-efficacy and self-concept (.68). Negative correlations were the following: maths anxiety and attitudes towards maths (-.7); trait anxiety and self-efficacy (-.24); and trait anxiety and self-concept (-.52). We created a path analysis of our significant results. In the analysis, negative self-concept was linked to lower self-efficacy and higher trait anxiety, and this system was connected to maths anxiety. The negative attitude towards maths was accompanied by higher maths anxiety. In addition, maths anxiety was tied to poor maths grades and therefore had a negative influence on school achievement.